Teacher Professional Competence in Implementing Fiqih Learning Evaluation Activities - Kusumawati, Rani; Sari, Fani Rahma; Nurlathyfa, Aulia; Al Hidayah, Ni’matul Fitriya (Journal of Quality Assurance in Islamic Education (JQAIE), 2024)
This research aims to describe the process of implementing learning evaluations carried out by class VII fiqh teachers at MTs NDM Surakarta and learn more about teacher competence in preparing learning plans, implementing learning, and conducting learning evaluations. The research type was descriptive qualitative; data was obtained by interviewing one of the teachers at MTs NDM Surakarta. Data analysis is based on the research objectives: teachers already have good competence in planning, implementing, and evaluating learning, so the learning outcomes obtained at this school also increase.